A gas-phase synthesis of Ag-centered phenylenediamine clusters. Issue 30 (9th July 2020) - Guo, Mengdi; Yin, Baoqi; Huang, Benben; Wu, Haiming; Luo, Zhixun
Abstract : Gas-phase synthesis of Ag-centered phenylenediamine clusters is achieved by dual sources combined with a flow tube reactor, producing Raman-active soft-landing deposits. Abstract : Small Ag n + clusters were prepared using a customized magnetron sputtering (MagS) cluster source, and their reactions with aromatic amine molecules were observed using a reflection time-of-flight mass spectrometer (TOF-MS). Interestingly, it was found that o -phenylenediamine (OPD) and m -phenylenediamine (MPD) readily reacted with the small Ag n + ( n = 1–3) clusters, resulting in the formation of [Ag(OPD)1–2 ] + and [Ag(MPD)1–3 ] + complexes. In contrast, p -phenylenediamine (PPD) was relatively inert with reaction products rarely being observed. Employing DFT calculations, we illustrated the altered electrostatic interaction distribution and orbital overlap correlation, which account for the diversity in forming N–Ag + –N complexes or simply hosting a metal ion around the aromatic ring. Further, utilizing the soft-landing deposition technique, we prepared mass-selected cluster deposits and conducted a Raman spectroscopic study.